A composite indicator to measure sustainable water use in Portugal: A compromise programming approach - Costa Freitas, Maria de Belém (2022)
Clean water is an important resource for maintaining human life, economic activities, and ecosystems’ survival. Nevertheless, its irregular distribution and occasional scarcity lead to the need to promote its sustainable use. To assess the current situation and the dynamics of sustainable water use, it is crucial to identify the main factors affecting it and to propose monitoring indicators. This paper develops an approach based on compromise pro gramming to analyse water use sustainability at the municipal level, with a methodology that comprise a framework designed in five steps: 1 – indicators’ choice; 2 – indicators’s weights; 3 – definition of sustainability rankings with the application of a compromise programming approach; 4- application of a GIS analysis; 5 – identification of the main factors affecting sustainable water use. As a first result, the consensus weights of the chosen indicators were defined, indicating that the most important internal factors affecting sustainable water use are safe water, the percentage of housing served by water supply and water distributed by inhabitant. Then sustainability rankings at the municipality level were defined considering these factors. Finally, it was possible to conclude that tourism activity, income level, and young age population have a significant negative effect on sustainable water use, and municipal revenue has a positive effect. Irrigated farming shows a non-significant negative effect on sustainable water use. Population density, elderly population and education level did not show the expected effects on sustainable water use.